2014
DOI: 10.1080/09205063.2014.927300
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of zwitterionic carboxybetaine materials and their derivatives

Abstract: Zwitterionic polycarboxybetaine (pCB)-based materials have drawn special attention due to their outstanding properties of resisting proteins adsorption, biofilm formation and cell attachment on a variety of substrates and surfaces, reducing the uptake of pCB-coated nanosized materials, as well as providing the capability of further functionalization. Zwitterionic pCBs have been proven to be excellent choices for many applications, not only limited to the field of antifouling. This review will summarize the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 95 publications
1
56
0
Order By: Relevance
“…In addition, MPC and MPC polymers have been commercialized worldwide as reagents and as base of new polymer designs with even better performance or novel features. Recently, MPC polymer‐like zwitterionic polymers, such as those based on sulfobetaine and carboxybetaine, have been synthesized and evaluated as the potential for biomaterials . It is expected that continued research into polymer biomaterials will advance minimally invasive medical care and regenerative medicine in support of an aging society.…”
Section: Notes and Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, MPC and MPC polymers have been commercialized worldwide as reagents and as base of new polymer designs with even better performance or novel features. Recently, MPC polymer‐like zwitterionic polymers, such as those based on sulfobetaine and carboxybetaine, have been synthesized and evaluated as the potential for biomaterials . It is expected that continued research into polymer biomaterials will advance minimally invasive medical care and regenerative medicine in support of an aging society.…”
Section: Notes and Future Perspectivementioning
confidence: 99%
“…Recently, MPC polymer-like zwitterionic polymers, such as those based on sulfobetaine and carboxybetaine, have been synthesized and evaluated as the potential for biomaterials. 67,[123][124][125][126][127] It is expected that continued research into polymer biomaterials will advance minimally invasive medical care and regenerative medicine in support of an aging society.…”
Section: Notes and Future Perspectivementioning
confidence: 99%
“…CB has been used in a range of biotechnological applications, above all as cryoprotectant [8,9]. It has been suggested that this modified amino acid has the capacity to form hydrogen bonds with a range of organic and inorganic acids that are likely to be responsible for the ascertained CB properties in supporting the adhesion and proliferation of several types of cells [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…88 More recently, zwitterionic materials have emerged as an excellent alternative to PEGylation. 89,90 The term zwitterion comes from the German word zwitter meaning hybrid and the word ion. 91 A zwitterion describes a molecule composed of two or more functional groups of which at least one has a positive and one has a negative electrical charge, but the net charge of the entire molecule is zero (Figure 1.4).…”
Section: Mitigating the Foreign Body Responsementioning
confidence: 99%
“…This inherent antifouling characteristic has led to various studies including glucose sensing in 100% blood serum, 58,113 antigen detection in complex media, 115 and prolonging the blood circulation time of coated drugs 6 among others. 89,116 Zwitterionic polymers are not only able to achieve an ultra-low fouling surface, but they are capable of resisting the FBR in vivo. 80 This advantage makes zwitterion-based materials uniquely suited for applications that involve implantation and prolonged use in the body.…”
Section: Zwitterionic Polymer Fabricationmentioning
confidence: 99%